PELAKSANAAN KLINIK SANITASI LINGKUNGAN PUSKESMAS JALAN GEDANG KOTA BENGKULU - Eva Oktavidiati; Sandos Yedilau; Nopia Wati; Riska Yanuarti (Public Health Department, Faculty of Health Science University Muhammadiyah Bengkulu, 2022)
Sanitation clinics are created to improve the health status of the community through promotive, preventive, and curative efforts that are carried out in an integrated, focused and continuous manner. This study aims to see the implementation of a sanitation clinic at Jalan Gedang Health Center. This research is a qualitative research with a descriptive approach that describes the state of the object under study. The data collection used is by interview and observation with interview guidelines and observation sheets. Informants in this study were sanitarian officers, poly officers, head of RT, community, head of Jalan Gedang Public Health Center. This research was conducted on August 10 s.d. August 20, 2022 in the Working Area of ​​Jalan Gedang Health Center, Bengkulu City. The results of the research in the Working Area of ​​Jalan Gedang Health Center showed that there were 2 activities that had been going well and in accordance with the Minister of Health Regulation No. 13 of 2015, namely there had been counseling activities carried out by the Puskesmas in order to solve health problems due to the environment and the Puskesmas had several field review programs. namely IKL SAB, TTU Sanitation, Healthy Homes, and Drinking Water Depot Sanitation. There is 1 sanitation clinic activity at the Puskesmas that is not appropriate, namely intervention activities in the community which are only carried out if a case has occurred in the community. The conclusion of this study is that Jalan Gedang Health Center has several programs that function in preventing environmental-based diseases. However, intervention programs in the community must be implemented better before environmental-based disease cases arise.